2010
DOI: 10.3844/ijrnsp.2010.29.38
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study: Colorectal Cancer Related Educational Program for Korean Americans

Abstract: Problem statement: The purpose of this study was to assess feasibility and acceptability of Colorectal Cancer (CRC) related educational program, specifically designed to promote Fecal Occult Blood Test (FOBT) completion for Korean Americans aged 50 years and older. Approach: Focus group discussion (N = 9) guided by semi-structured questions was conducted to understand the demand for CRC education and to obtain feedback on overall content, language and delivery media for a preliminary version of the educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Across several studies, an estimated 48 to 78% of KA women reported ever having had a mammogram in their lifetime (Lee et al, 2016;Choi et al, 2017;Chawla et al, 2015;Choi et al, 2010;Hoeffel et al, 2012;Kim et al, 2010a;Lee et al, 2009). Unfortunately, these rates are not comparable across studies because of differing operational definitions of mammography use.…”
Section: Introductionmentioning
confidence: 99%
“…Across several studies, an estimated 48 to 78% of KA women reported ever having had a mammogram in their lifetime (Lee et al, 2016;Choi et al, 2017;Chawla et al, 2015;Choi et al, 2010;Hoeffel et al, 2012;Kim et al, 2010a;Lee et al, 2009). Unfortunately, these rates are not comparable across studies because of differing operational definitions of mammography use.…”
Section: Introductionmentioning
confidence: 99%